A study on the factors influencing old age identity among the Chinese elderly - Yu, Xiao; Wang, Qihui (Frontiers in Public Health, 2023)
Old age identity is the self-perception of when old age begins, reflects public age values and acceptance of aging. Different from Western countries, China is a country with a long-standing culture of respect for the elderly and filial piety norms, and the influence of the cultural background on the old age identity is worthy of attention. Using the 2014 China Longitudinal Aging Social Survey (CLASS), this study focuses on the old age identity of the Chinese elderly and its influencing factors. A total of 7,400 participants answered questions about old age identity. The average old age identity of Chinese people aged 60 and above is 70 years. Health status, psychological status, behavior, socioeconomic status, and some demographic characteristics significantly affect the old age identity of the Chinese elderly. The traditional Chinese cultural background of respect for the elderly and the norms of filial piety have an impact on the old age identity of the Chinese elderly through family intergenerational support. The various forms of support provided by children to the elderly can help them achieve a positive age identity—enter old age later, raise the likelihood of identification with non-elderly groups, and reduce aging degree. The number of children of the elderly, the children’s economic conditions and care support for grandchildren have negative effects. A positive old age identity can help the elderly improve their self-esteem. Our study has great practical and policy significance for actively responding to the aging society.